Implementasi Penyelesaian Sengketa Pertanahan Melalui Mediasi Oleh Kantor Pertanahan Kota Medan - Martha, Andhyka; Ramadhan, M. Citra; Zulyadi, Rizkan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This article aims to analyze land problems that arise from economic, social and cultural aspects and even religion. For this reason, the issue of non-litigation land dispute resolution, especially mediation, is very interesting. The research method used is applied law research which combines two normative-empirical legal studies. The starting point of this research itself departs from the problem of typology of land disputes in the city of Medan and the resolution of land disputes through mediation by the Medan City Land Office as well as obstacles in resolving land disputes through mediation at the Medan City Land Office? The results showed: First, the typology of land disputes that occurred in the city of Medan was based on problems, land tenure and ownership, procedures for determining land rights and registration, boundaries and/or location of land parcels, land reform objects, land acquisition, and implementation of court decisions; Second, the settlement of land disputes through mediation by the Medan City Land Office based on the Regulation of the Minister of Agrarian Affairs and Spatial Planning No. 21 of 2020 concerning Handling and Settlement of Land Cases is related to the Decree of the Head of the National Land Agency of the Republic of Indonesia Number 34 of 2007 concerning Technical Guidelines for Handling and Settlement of Land Problems Jo. Technical Instructions No. 05/Juknis/d.v/2007 concerning Mechanism for Implementation of Mediation; Third, the obstacles in resolving land disputes through mediation at the Medan City Land Office can be seen from the aspects, legal substance, legal structure and legal culture. The results of the study reveal that there is a need for improvement in laws and regulations related to the formation of legal rules that guide the implementation of land dispute resolution through integral and comprehensive mediation and human resources (peace maintenance). legal culture in increasing public legal awareness.